2016
DOI: 10.1016/j.ijcard.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Reported cardiac phenotypes in hereditary hemorrhagic telangiectasia emphasize burdens from arrhythmias, anemia and its treatments, but suggest reduced rates of myocardial infarction

Abstract: Arrhythmias are the most common cardiac phenotype in HHT, and likely to be aggravated by iron deficiency anemia, its treatments, and/or high output states due to AVMs. Myocardial infarction rates may be reduced in this apparently high risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 51 publications
0
16
1
Order By: Relevance
“…Additionally, screening methods and treatment options for PAVMs, CVMs, epistaxis, gastro-intestinal bleeding and subsequent anemia have improved over the years, which most likely benefits survival as well. In addition to this, several studies have suggested that patients with HHT possibly have a natural protection against certain cancers and myocardial infarction, possibly benefiting survival rates [19,20]. While we did not observe a negative effect of HHT on the survival in this study, it is important to realize that the quality of life in these patients will probably still be lower compared to their controls even if optimal screening and treatment was performed.…”
Section: Discussioncontrasting
confidence: 46%
“…Additionally, screening methods and treatment options for PAVMs, CVMs, epistaxis, gastro-intestinal bleeding and subsequent anemia have improved over the years, which most likely benefits survival as well. In addition to this, several studies have suggested that patients with HHT possibly have a natural protection against certain cancers and myocardial infarction, possibly benefiting survival rates [19,20]. While we did not observe a negative effect of HHT on the survival in this study, it is important to realize that the quality of life in these patients will probably still be lower compared to their controls even if optimal screening and treatment was performed.…”
Section: Discussioncontrasting
confidence: 46%
“…Patients with HHT often tolerate anticoagulation or antiplatelet therapy well 49. Recently described reduced rates of specific cancers,34 50 51 better survival outcomes for cancer patients who have HHT52 and low myocardial infarction rates20 await explanation. The HHT phenotype is subtly different between HHT genotypes, for instance patients with HHT2 are less likely to have PAVMs and more likely to have hepatic AVMs than patients with HHT1 or SMAD4 -related HHT 37 39.…”
Section: Introductionmentioning
confidence: 99%
“…As these telangiectasia often occur in the nasal mucosa, the most prominent clinical feature of HHT is epistaxis [ 12 ], 96% of patients with HHT suffer from epistaxis, of which more than 50% before the age of 20 [ 13 ]. Both epistaxis and especially gastrointestinal bleeding can lead to severe anaemia [ 14 ].…”
Section: Hereditary Haemorrhagic Telangiectasiamentioning
confidence: 99%